Organization-Managerial Mechanism of Shaping Human Capital in Organization Based on Knowledge Management - I. G. Gorina (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
Today organization competitiveness depends mainly on the development of HR potential and the process of labour resource management. In personnel training the process of knowledge management is on the foreground, its introduction can render positive effect both on production process and HR management of the organization. The article pays special attention to the definition of such notions as ‘knowledge’, ‘knowledge management’, ‘development of HR potential’, shows academic activity in this field in 2018–2022 on the part of home authors and finds interconnection between the process of knowledge management and development of HR potential. The author analyzed and systematized key trends of the subject area. Findings of the research demonstrate that for home scientists the problems of attracting highly-qualified personnel and adaptation of HR potential to organizational transformations are especially acute. According to Elibrary.ru data the biggest number of studies dealing with knowledge management and development of HR potential during the last 5 years were carried out in the field of education, digitalization and HR management.